Tinjauan Fiqh Muamalah pada Praktik Sewa Jasa Laundry Syariah Arransha - Dewi Indrayani (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2021)
Abstract This study aims to discuss about how the practice of sharia laundry services in Arransha Langsa City? And how is the fiqh muamalah review of the practice of syari'ah laundry services in Arransha Langsa City?. This study uses qualitative methods with descriptive and empirical analysis and data collection methods by observation, interviews and documentation. The results of this study explain that the practice of Arransha sharia laundry services in Langsa City is in accordance with laundry procedures in general, but the emphasis is on the practice of Arransha sharia laundry services that have not used the overall thaharah concept. Holiness is part of faith. The condition for the validity of prayer is that the body, clothes and place of worship are clean. Based on the fiqh muamalah review of Arransha's laundry practice, it has not fulfilled the fiqh muamalah elements such as a violation of the contract stated in the bill of lading, namely compensation for goods by 50%, but in reality this is not the case. The Arransha sharia laundry party did not fulfill it as agreed. The advice that researchers can give is that the Arransha sharia laundry party should provide compensation (Dhaman) for damaged or lost consumer goods as agreed in the contract. Keywords: Rent, Syari'ah Laundry and Fiqh Muamalah